ARRANGEMENT OF PEDESTRIAN PATHS BASED ON WALKABILITY ASPECTS IN JAKARTA KOTA TUA AREA - Khairunnisa, Siti Azizah; Rukmi, Wara Indira; Kurniawan, Eddi Basuki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
Jakarta Kota Tua's (old town) Area is a historical area that located in Capital City of Indonesia, namely Jakarta which continues to degrade in both physical and nonphysical ways, resulting in an unfavorable image and an unappealing location, one of which is the lack of pedestrian facilities in the Kota Tua area, not to mention the fact that during the holidays, pedestrians are jammed with street vendors, making it impossible for pedestrians to walk in the area around the Old Town Area. Furthermore, there are still neglected facilities such as trash cans and bus stations where passengers can wait for buses that are not fit for their intended purpose. This research aims to find out the walkibility based on existing condition in the Jakarta Kota Tua area. The analytical method that uses in this research is descriptive analysis based on pedestrian path characteristic walkability index analysis. According to the calculation results, 1st zone is included in the waiting to walk category with a walkscore value of 56.3 and there are segments that have the lowest scores, namely segments 12 A and 12 B. Meanwhile, 2nd zone is included in the category of walk on your own risk because it has a walks score of 48,31 which is below the score of 1st zone or in other words it is necessary to improve in terms of quality and quantity as well as control for side barriers which aim to ensure that visitors or pedestrians are not disturbed and feel comfortable during their activities.